2013
DOI: 10.1002/jbm.b.32908
|View full text |Cite
|
Sign up to set email alerts
|

Novel albendazole–chitosan nanoparticles for intestinal absorption enhancement and hepatic targeting improvement in rats

Abstract: To improve the treatment of helminthiasis, filariasis, and colorectal cancer, albendazole-associated chitosan nanoparticles (ABZ-CS-NPs) were prepared using the emulsion crosslinking volatile technique with contained sodium tripolyphosphate as the crosslinking agent and Poloxamer 188 as the auxiliary solvent. The structural characteristics of the NPs were determined using X-ray diffraction to analyze the interaction between CS and the drug. The NPs were then evaluated in terms of their physicochemical characte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 34 publications
2
15
0
Order By: Relevance
“…In Table 1 are shown the summary of the characteristics of the loaded and unloaded NCs and NEs, including the association efficiency and loading capacity. The association efficiency values determined correspond well with those measured in previous studies using chitosan-tripolyphosphate nanoparticles that lied in the range of 79.57 ± 0.96% and 13.38 ± 0.44% for the loading capacity [37].…”
Section: Resultssupporting
confidence: 86%
“…In Table 1 are shown the summary of the characteristics of the loaded and unloaded NCs and NEs, including the association efficiency and loading capacity. The association efficiency values determined correspond well with those measured in previous studies using chitosan-tripolyphosphate nanoparticles that lied in the range of 79.57 ± 0.96% and 13.38 ± 0.44% for the loading capacity [37].…”
Section: Resultssupporting
confidence: 86%
“…Marslin et al reported in 2017 the preparation of ABZ-loaded solid lipid nanoparticles (SLN) which induced the slow release of the drug over a 24 h time period in phosphate buffer (pH = 7.4) reaching an 82% cumulative drug release [15]. Another study was published by Liu et al in 2013 regarding the synthesis of ABZ-loaded chitosan nanoparticles which were tested in acidic, slightly acid and neutral environments, respectively; the chitosan-nanoparticles revealed a similar behavior to our nanoformulations with the drug's highest dissolution in acid medium and a sustained release of the drug following encapsulation [69]. Similar results were also reported by Panwar et al in 2010 who prepared ABZ-loaded liposomes which revealed the sustained release of the drug over a 4.5 h period in slightly acid phosphate buffer (pH = 5.6) [70].…”
Section: Discussionsupporting
confidence: 56%
“…1). Our goal was to prepare ABZ nanocrystals with size distribution parameters similar to those, produced by novel modified variant of the so-called emulsion crosslinking volatile method [33,34].…”
Section: Introductionmentioning
confidence: 99%